Knowledge of Human Genome Project among Dentistry undergraduates - Daniela Peressoni Vieira; Thaisa Cezária Triches; Marcos Ximenes Filho; Ana Paula Silveira Caldeira de Andrada Beltrame; Leila Posenato Garcia; Mabel Mariela Rodríguez Cordeiro (Revista Sul-Brasileira de Odontologia, 2015)
The Human Genome Project (HGP) has allowed for advances in diagnosis and prevention of diseases. Objective: The aim of this study was to investigate the knowledge of undergraduates from the Federal University of Santa Catarina, regarding HGP and its applicability. Material and methods: Thirty-one students were interviewed by using a questionnaire with open questions, followed by qualitative and quantitative analysis through answers’ grouping. Results: Only 4.5% did not know HGP, while most of them (83%) demonstrated knowledge gained from the media. Only 21% cited the undergraduate program as a source of information, 56% recognized advances in disease prevention and 81% reported applicability in Dentistry. 97% students would give blood samples for research, 28% reported concern about misuse of this information, while 31% did not report any disadvantage. Conclusion: It may be concluded that the students have some knowledge on HGP. However, it is not widely discussed during course, because the media was the main source of information.